Grain supply–demand in countries along the “Belt and Road” from 1993 to 2021: spatiotemporal evolution, match, security and driving mechanism - Qu, Weijuan; Tang, Xiantao; Zhang, Xufang; Li, Guohao; Zhang, Jiahui; Song, Xiaotong; Zhao, Minghua; Han, Rongqing (Frontiers in Sustainable Food Systems, 2024)
Introduction The grain supply-demand balance is a long-standing concern for many countries and is essential to guaranteeing social stability, maintaining economic development and ensuring national grain security. Methods Based on the data of 65 countries along the “Belt and Road” (B&R) from 1993 to 2021, this paper analyzed the spatiotemporal evolution, the matching relationship, regional grain security situation and driving factors of grain supply-demand by measuring and classifying the grain self-sufficiency rate using methods such as geostatistical analysis and the GTWR model. Results The results indicated the following: (1) The B&R region was still at the primary stage of “food-based and feed-supplemented”. Grain supply and demand in the B&R region showed a steady upward trend, with grain yield contributing more to grain supply than sown area. (2) Overall, the B&R region has been largely self-sufficient since 2007, with grain supply meeting demand, but the level of grain self-sufficiency varied considerably between countries. (3) More than 58% of the countries were in grain insecurity, concentrated in West Asia-Middle East and South-East Asia. The gravity center of both grain supply and demand was near East Asia. (4) In terms of matching supply-demand, most countries fell into the category of high supply-high demand and low supply-low demand, with basically the same level of grain supply and demand. (5) Grain yield had the largest positive impact on grain supply-demand, GDP had the largest negative impact, and temperature change and precipitation change had a relatively small effect. The effects of fertilizer use, grain yield, and GDP on grain supply-demand fluctuated greatly over time. Discussion These findings can provide a scientific basis for the country to formulate policies for a sustainable grain supply-demand system.